Quantitative real-time PCR assays for detection and quantification of all seven Eimeria species that infect the chicken - Vrba, Vladmir; Blake, Damer P; Poplstein, Martin (Veterinary parasitology, 2010)
The development and validation of real-time quantitative PCR (qPCR) assays specific to all seven Eimeria species that cause coccidiosis in the chicken is described. The presented work utilizes previously published assays for Eimeria maxima, E. necatrix and E. tenella and adds assays for E. acervulina, E. brunetti, E. mitis and E. praecox. These assays target unique single copy sequences derived from sequence characterized amplified region (SCAR) markers. All seven qPCR markers were sequenced from multiple strains and confirmed to be non-polymorphic and identical to the original SCAR sequence. Sequences conserved within each species were chosen with the aim of developing genuinely universal markers, providing global coverage. An exact match for the primers and TaqMan(®) probe during PCR cycling enables precise relative quantification of multiple species in a mixture regardless of the strains present. All markers utilized in these qPCR assays are absolutely species-specific and support reproducible quantification across a wide linear range, unaffected by the presence of non-target species or other contaminating DNA. The sensitivity of these assays indicates that DNA equivalent to a single sporulated oocyst can be consistently detected. These assays will be a valuable tool from both industry and research perspectives. Comparison of our panel of qPCR assays with results derived by microscopy, the traditional Gold Standard, using poultry farm field samples support their efficacy.
Keywords: polymerázová řetězová reakce; Species Specificity; Coccidiosis; druhová specificita; Animals; Poultry Diseases; kokcidióza; kur domácí; nemoci drůbeže; Eimeria; zvířata; Chickens; Polymerase Chain Reaction